The Effects of short term L-citrulline supplementation in the immediate preparation period on the blood morphotic indicators in the population of amateur runners - Słojkowska, Agnieszka; Kruber, Karolina; Stankiewicz, Błażej (Journal of Education, Health and Sport, 2025)
Background and Study Aim: The main aim of the study was to asses the effects of short term L-citrulline supplementation in the immediate preparation period on the blood morphotic indicators in the population of amateur runners. Material and Methods: Population of 24 physically active semi-professional runners preperign for the long distance runn were assigned to two groups to determine the effect of 14-days of 6000 mg per day cytruline supplementation in the immediate preparation period on the blood morphotic indicators in the population of amateur runners. The study was completed by 12 subjects receiving 6 000 mg per cytruline daily (in six 1g gelatin capsules), and 10 subjects receiving placebo gelatin capluses fulfilled with potato flour. The morphological blood parameters were messured from the venous blood collected into 5-ml tubes containing EDTAK2 as the anticoagulant before and after two weeks of supplementation. Results: There were no significant differences found between the groups with respect to changes in the levels of the studied parameters, except for creatine kinase.